1992
DOI: 10.1111/j.1365-2249.1992.tb05839.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased CD11/CD18 expression on peripheral blood leucocytes of patients with sarcoidosis

Abstract: SUMMARYSarcoidosis is a tnultisystem disease of unknown etiology characterized by non-caseating granulomata, formed mainly from macrophages surrounded by lymphocytes and plasma cells. Using a novel method for the preparation of blood leucocytes for flow cytometry, we report increased expression of LeuCAMs (CD 11/CD 18) on peripheral blood leucocytes of 11 Caucasian and 10 Afro-Caribbean patients with sarcoidosis compared with age-, sex-and race-matched controls. Whilst the percentages ofthe cells expressing CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
21
1

Year Published

1994
1994
2001
2001

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 36 publications
5
21
1
Order By: Relevance
“…Eleven were AfroCaribbean, mean age 36 years (range 21-63 years) and 12 were Caucasian, mean age 36 years (range 27-54 years). Nineteen of the patients were included in a previous study [4]. Patients were not receiving corticosteroids or other immunosuppressive therapy at the time of investigations or within the previous 12 months.…”
Section: Study Populationmentioning
confidence: 99%
See 4 more Smart Citations
“…Eleven were AfroCaribbean, mean age 36 years (range 21-63 years) and 12 were Caucasian, mean age 36 years (range 27-54 years). Nineteen of the patients were included in a previous study [4]. Patients were not receiving corticosteroids or other immunosuppressive therapy at the time of investigations or within the previous 12 months.…”
Section: Study Populationmentioning
confidence: 99%
“…Clinical information obtained from the patients included smoking habits, chest x-ray findings, graded according to conventional criteria (Stage I, hilar adenopathy without parenchymal infiltrates; Stage II, hilar adenopathy with parenchymal infiltrates; and Stage III, fibrosis or infiltrates without hilar adenopathy), symptom duration and organ involvement, SACE levels and erythrocyte sedimentation rate (ESR) as well as lung function tests. This information was obtained for tests done within 1 week of the blood being taken for the study reported here and elsewhere [4]. Clinical information on 19 of these patients has previously been reported [4].…”
Section: Study Populationmentioning
confidence: 99%
See 3 more Smart Citations